Peralihan Kredit Pemilikan Rumah (KPR) Dari Pembeli Pertama Ke Pembeli Kedua di Bank BTN KC Cikarang dengan Akta Notaris - M. Ilham Akbar Sadewa; Prihati Yuniarlin (Jurnal Preferensi Hukum, 2024)
This study is about the transfer of home ownership credit from the first buyer to the second buyer because having a home is the right of every human being, especially the Indonesian people. This study uses a normative legal research method, namely a study that examines based on the principles, norms and rules of laws and regulations. The research materials used in this study are primary and secondary legal materials and the results of the study are analyzed prescriptively using the deductive method, namely general data on legal concepts, both expert opinions and legal facts to study and then provide a justification assessment of the object being studied. Legal protection is given to customers who transfer home ownership credit (KPR) at BTN Cikarang bank through the BTN Cikarang bank procedure, namely the termination of all rights from the first party and transfer to the second buyer in this case the new customer and the legal protection obtained from the second buyer who transfers home ownership credit without the bank's knowledge and through a notary in the form of an authentic deed made by a notary with notification to BTN Bank Kc Cikarang and the authentic deed of PPJB becomes the basis for AJB so that the second buyer can safely change the name of the certificate.